Deteksi Pengenalan Pola Lingkaran Menggunakan Metode Ekstraksi Ciri Citra pada Parameter Metric - Maisura Ningrum; Nurul Fadillah (Jurnal SIFO Mikroskil, 2018)
Shape is one of the characteristics that can be extracted from an object. This feature can be used to distinguish between objects with each other. The following is an example of image processing to detect circular objects. One parameter that can be used to define a circle shape is metric. Metric is a comparison between the area and circumference of an object. Metric values range from 0 to d. 1. Objects are circular, the metric value is close to one. The results of image processing indicate that the method used can detect objects that are in a fairly good circle. The purpose of the construction of this system is to make a program of introducing circle patterns using the characteristic extraction method in the metric parameter.